Evaluation of the Implementation of the Stunting Prevention and Handling Program in Labuhan Bajo Village, Sumbawa Regency - Has’ad Rahman Attamimi; Yunita Lestari; Evi Gustia Kesuma; Yulida Anggraini (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is a chronic condition characterized by impaired physical growth resulting from prolonged malnutrition. It is clinically defined as a height-for-age measurement more than two standard deviations below the median of the WHO Child Growth Standards. The primary contributor to stunting is poor nutritional status during critical growth periods. Thus, monitoring the nutritional status of infants and toddlers is essential, as malnutrition during these stages can lead to permanent damage to both physical and cognitive development. This study used a qualitative research design to evaluate the implementation of the stunting prevention and control program in Labuhan Bajo Village, located in Utan District, Sumbawa Regency. The research subjects were Labuhan Bajo Village, and the research object was the local stunting prevention and control program. Data collection methods included observation, document review, and in-depth interviews. Data analysis followed an interactive model to interpret the qualitative findings. The findings showed that all the evaluation indicators assessed were implemented well. These indicators included: (1) Input indicators, (2) Process indicators, and (3) Output indicators. However, the output indicators revealed certain deficiencies. Despite the program’s efforts, the prevalence and risk of stunting in children in Labuhan Bajo Village remained relatively high. Contributing factors included the large number of young couples, an increase in adolescents of childbearing age, unhealthy environmental conditions, and a low level of public awareness about the importance of balanced nutrition. This suggests that while the program had positive impacts on several fronts, improvements are still needed to address the root causes of stunting. Enhancing public awareness and addressing the broader social determinants of health will be crucial in reducing stunting rates and improving the overall effectiveness of the program in the future.